Comparison between myopia versus hypermetropia with progressive addition lenses in computer users - Abdul Hanan Shahid; Muhammad Anwar Awan; Aamer Ejaz Khan Niazi (Medical Journal of South Punjab, 2025)
Objective: To compare the effect of  myopia versus hypermetropia on the quality of vision  with progressive addition lenses in computer usersMethodology: It was a comparative cross-sectional study conducted from December 2023 to May 2024 at Keratoconus and Low Vision Clinic, Eye 2 Eye Optometrist, Lahore. The study involved 64 participants aged between  40-55 years After assessing the patient's distant and near visual acuity. A questionnaire was adopted to evaluate the satisfaction level of visual performance based on the respondents’ daily activities and was given after 6 months. There were three parts of the questionnaire; namely (1) demographic details, (2) respondents' feedback, and (3) symptoms reported by the PALs wearers.  Questions regarding visual performances intermediate viewing and near vision with the total satisfaction of progressive additional lenses (PALs) prescribed were calculated using a Likert scale.Results: At 6 months Hypermetropia reported significantly better outcomes compared to those with Astigmatic Myopia, as indicated by a Chi-Square value of 6.46 (p=0.04).In terms of clear vision at different distances, The Chi-Square values were 5.78 (p=0.12) and 6.58 (p=0.16) respectively. The ease of adapting to PALs showed no significant variation across refractive errors, as evidenced by Chi-Square values from 1.47 (p=0.83) for Myopia to 7.53 (p=0.28) for Astigmatic Myopia. Regarding the improvement in computer work experience with PALs, the differences were not statistically significant between astigmatic myopia and hypermetropia. The Chi-Square values were 1.75 (p=0.42) for Myopia and 6.89 (p=0.14)Conclusion: PALs to individual refractive profiles can enhance the overall user experience, improve comfort, and address specific issues related to visual clarity, eyestrain, and posture.